Phenotyping Established Chronic Lung Allograft Dysfunction Predicts Extracorporeal Photopheresis Response in Lung Transplant Patients. Issue 4 (13th February 2013) - Greer, M.; Dierich, M.; De Wall, C.; Suhling, H.; Rademacher, J.; Welte, T.; Haverich, A.; Warnecke, G.; Ivanyi, P.; Buchholz, S.; Gottlieb, J.; Fuehner, T.
Abstract : Chronic lung allograft dysfunction (CLAD) remains the leading cause of mortality in lung transplant recipients after the first year. Treatment remains limited and unpredictable. Existing data suggests extracorporeal photopheresis (ECP) may be beneficial. This study aimed to identify factors predicting treatment response and the prognostic implications. A single center retrospective analysis of all patients commencing ECP for CLAD between November 1, 2007 and September 1, 2011 was performed. In total 65 patients were included, 64 of whom had deteriorated under azithromycin. Median follow‐up after commencing ECP was 503 days. Upon commencing ECP, all patients were classified using proposed criteria for emerging clinical phenotypes, including "restrictive allograft syndrome (RAS)", "neutrophilic CLAD (nCLAD)" and "rapid decliners". At follow‐up, 8 patients demonstrated ≥10% improvement in FEV1, 27 patients had stabilized and 30 patients exhibited ≥10% decline in FEV1 . Patients fulfilling criteria for "rapid decliners" (n = 21, p = 0.005), RAS (n = 22, p = 0.002) and those not exhibiting neutrophilia in bronchoalveolar lavage (n = 44, p = 0.01) exhibited poorer outcomes. ECP appears an effective second line treatment in CLAD patients progressing under azithromycin. ECP responders demonstrated improved progression‐free survival (median 401 vs. 133 days). Proposed CLAD phenotypes require refinement, but appear to predict the likelihood of ECP response. Abstract : Initiation of extracorporeal photopheresis in established chronic lung allograft syndrome confers survival benefi t in a majority of patients, with factors such as bronchoalveolar lavage neutrophilia, restrictive lung function and rate of decline in graft function predicting the likelihood of response. See editorial by Barr on page 833.